Premature birth associated with a favorable course in gestational alloimmune liver disease (GALD): A case report - Mulzer, Linda-Marie; Reutter, Heiko; Jüngert, Jörg; Knisely, A. S.; Schmid, Margit; Hoerning, André; Morhart, Patrick (Frontiers in Pediatrics, 2023)
Gestational alloimmune liver disease (GALD) is a rare neonatal disorder with high mortality and morbidity [1]. The patients come to caregivers attention aged a few hours or days. The disease manifests as an acute liver failure with or without siderosis [2]. The differential diagnostic of neonatal acute liver failure (NALF) is broad including mainly immunologic, infectious, metabolic and toxic disorders. The most common cause however is GALD followed by herpes simplex virus (HSV) infection [3, 4]. The best suited pathophysiological pardagim of GALD is this of a maternofetal alloimune disorder. State of the art treatment combines intravenously administered immunoglobulin (IVIG) with exchange transfusion (ET). We report on an infant born at 35+2 weeks’ gestation with a favorable course in GALD. Premature birth in our patient may thus have exerted protective aspects and lessened morbidity because intrauterine exposure to maternal complement-fixing antibodies was shortened [2]. Nevertheless the diagnosis of GALD-NH is challenging and difficult. Therefore, we suggest a flowchart combining clinical findings with histopathologic findings of the liver and lip mucosa biopsy and if available an abdominal magnetic resonance imaging-study focusing on the liver, spleen, and pancreas. This diagnostic workup must be followed by ET and subsequent administration of IVIG without delay.